2002
DOI: 10.1258/jrsm.95.12.604
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient clinic: where is the delay?

Abstract: In outpatient clinics, consultation times are often eroded by extraneous activities. We measured the components of each outpatient episode in 167 patients attending a general urology follow-up clinic. 41% of time in the clinic was spent away from the patient-administration 17%, disturbances 15%, finding results 9%. The inefficiencies had changed little since a study in the same setting thirteen years earlier. Since then, parallel nurse-practitioner-run clinics have been introduced in the hope of giving consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The same clinic was re-evaluated in 2001 and, despite some changes in the clinic organisation, they still found that 41% of the consultant's time was spent away from the patient. 16 The mean consultation time had reduced from 8.2 minutes to 4.8 minutes. The most easily addressed inefficiency was time spent looking for missing information, mainly radiology reports.…”
Section: Running An Outpatient Servicementioning
confidence: 96%
“…The same clinic was re-evaluated in 2001 and, despite some changes in the clinic organisation, they still found that 41% of the consultant's time was spent away from the patient. 16 The mean consultation time had reduced from 8.2 minutes to 4.8 minutes. The most easily addressed inefficiency was time spent looking for missing information, mainly radiology reports.…”
Section: Running An Outpatient Servicementioning
confidence: 96%
“…In 1988, the time spent with the patient in a urological outpatient clinic was 7.6 minutes on average. This decreased to 4.6 minutes in 2002 in spite of introducing time saving measures such as nurse-led clinics and one-stop clinics 40% was spent on administrative tasks [6]. In our own clinics before CRS, an average of 12 minutes total time per patient was scheduled.…”
Section: Discussionmentioning
confidence: 78%
“…To ease outpatient clinic pressures it was thought at the start of this millennium that an electronic patient data system might be the answer [6]. The Veteran Health Administration (VHA) in the USA had successfully introduced their Computerised Patient Record System (CPRS) and introduced it as a patient-centred approach to clinical computing rather than a department-centred approach [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems that provide patients with the ability to obtain their own results have been shown to be acceptable to patients and to save time among clinicians (Ridgeway et al 2000). Such a newly designed process should reduce the amount of time spent by clinic staff in information-gathering tasks and increase the time spent providing patient care (Patel et al 2002).…”
Section: Variancementioning
confidence: 99%